2011
DOI: 10.1097/wox.0b013e3182093cbb
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Chronic Respiratory Diseases (CRD) in Middle East and North Africa (MENA)

Abstract: Chronic respiratory diseases involve a heterogenous group of diseases, including, chronic obstructive pulmonary disease (COPD), asthma, sleep apnea syndrome, pulmonary hypertension, and many occupational diseases. They affect more than one billion people worldwide. Their medical, social, and economic impacts are heavy, especially in developing countries such as Middle East and North Africa countries, where they represent a public health problem. They are essentially represented by COPD, asthma, and allergic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…It is important to note that chronic respiratory disease burden, including asthma has continued to increase in Africa due to lack of appropriate response from the governments of many African countries (81,82). The national emphasis on asthma and relevant health messages have been sub-optimal, leading, in sequence, to poor awareness of the burden, low prioritization, inadequate staffing and resources, and very low budget allocation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that chronic respiratory disease burden, including asthma has continued to increase in Africa due to lack of appropriate response from the governments of many African countries (81,82). The national emphasis on asthma and relevant health messages have been sub-optimal, leading, in sequence, to poor awareness of the burden, low prioritization, inadequate staffing and resources, and very low budget allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) represents a major public health problem in developing countries and especially in North Africa [1]. It is characterized by lung function impairment with airway obstruction, and is currently estimated to be one of the leading causes of death in 2010 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although COPD is one of the leading causes of mortality and morbidity, epidemiological data on COPD are very limited in North Africa, including Tunisia. The comparison of the few Tunisian COPD prevalence estimates with the international literature showed that estimated prevalence of COPD in Tunisia was low compared with America and Europe and the disease is certainly under diagnosed [1]. In fact, National estimates of COPD prevalence are usually based on self-reported diagnosis without the use of objective measurement of lung function by spirometry testing.…”
Section: Introductionmentioning
confidence: 99%
“…This has often led to delay in the diagnosis till the disease becomes clinically apparent or is in an advanced stage. [29] There are conflicting data about smoking in the region; however, prevalence of smoking in men varies between 20% in Iran and 63% in Turkey. [30] This was also reflected in a recently released report by the WHO about the global tobacco epidemic that showed prevalence of smoking in the Middle East ranged from 38.5% in Lebanon to 62.0% in Syria.…”
Section: Epidemiologymentioning
confidence: 99%
“…The main risk factors for COPD in the Middle East are considered to be tobacco smoke, passive smoking, and other indoor and outdoor air pollutants. [2229] In this region, COPD affects more people with low socioeconomic status, as smoking is more prevalent among illiterate people. [223334] Environmental factors, such as indoor air pollution from biomass fuel used for cooking and heating, appear to contribute to COPD in women.…”
Section: Epidemiologymentioning
confidence: 99%